Tracing El Greco's Echoes of Antiquity: Audience Interaction with Online Art - Pericleous, Pericles; Assimakopoulou, Ianthi; Ioannou, Andri; Fidas, Christos; Avouris, Nikolaos (Association for Computing Machinery, 2021)
This paper discusses the design and evaluation of a tool to provide interactive museum experiences to visitors. It is an online application that enables the juxtaposed presentation of two works of art from different historical periods and artistic environments and the tracing of similar elements they share (forms, motifs, gestures, compositional details etc.). The aim of this application is to allow the exhibition curator and the art historian to evaluate the choices made by the audience, concerning works of art, related to an exhibition project. It will also conduce to increase the attractiveness of art exhibitions for the general public, as the application may arouse interest and contribute to the better understanding of the creative process and the compositional elements of works of art. First, we identify the scope of the challenge and explain basic concepts and definitions relating to interaction with works of art. Then, the design and functionality of the application are discussed. This is followed by the description of the conducted study and interpretation of the results. An eye-tracking study involved interaction of 63 participants of mixed background with 21 pairs of art works from the exhibition “Echoes of Antiquity in the Oeuvre of Domenikos Theotokopoulos”. Finally, a few suggestions for future research are made, based on the conclusions drawn.
Keywords: Django; art appreciation; curators; eye-tracking; history of art; museums; visual perception; web application